Influencing factors of participation in and satisfaction with elderly health checkups: a cross-sectional study - Chen, Ying-Jen; Lin, Chiou-Fen; Feng, Jie; Chiu, Huei-Ling (Frontiers in Public Health, 2023)
Background: Attending health checkups as a primary prevention strategy benefits the elderly in facilitating the identification of health issues and risk factors for disease. Little is known about factors influencing participation and satisfaction with a free annual elderly health checkup program (EHCP) in Taiwan. This study aimed to extend current knowledge related to the uptake of this service and individuals’ views of the service. Methods: This was a cross-sectional study using a telephone interview survey method to compare influencing factors and satisfaction between participants and non-participants of an EHCP. The individuals involved were older adults in Taipei, Taiwan. The random sampling method included 1100 people, 550 older adults who had participated in the EHCP within the last 3 years, and 550 older adults who had not. A questionnaire containing personal characteristics and satisfaction with the EHCP was used. Independent t-test and Pearson’s Chi-squared test were used to evaluate differences between the two groups. Associations between individual characteristics and health checkup attendance were estimated using log-binomial models. Results: Results showed that 51.64% of participants reported being satisfied with the checkups; however, only 41.09% of non-participants were satisfied. In the association analysis, age, educational level, chronic diseases, and subjective satisfaction were related to older persons’ participation. Furthermore, having a stroke was associated with a higher attendance rate (prevalence ratio: 1.49; 95% confidence interval: (1.13,1.96)). Conclusions: The EHCP had a high proportion of satisfaction among participants, but the proportion was low among nonparticipants. Several factors were associated with participation and might lead to unequal healthcare service uptake. Health checkups need to increase among people at a young age, those with low educational backgrounds, and those without chronic diseases.